2004
DOI: 10.1016/s0014-5793(04)00231-5
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to transglutaminase of gliadin peptides predicted by a mass spectrometry‐based assay

Abstract: A peptidomics approach was developed to identify transglutaminase-susceptible Q residues within a pepsin^trypsin gliadin digest. Based on tagging with a monodansylcadaverine £uorescent probe, six K K/L L-, Q Q-gliadin, and low molecular weight glutenin peptides were identi¢ed by nanospray tandem mass spectrometry. In functioning as an acyl acceptor, tissue transglutaminase was able to form complexes with the glutamine-rich gliadin peptides, whereas by lowering pH, the peptides were deamidated by transglutamina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
51
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 18 publications
0
51
0
1
Order By: Relevance
“…These in vitro studies identified stimulatory gluten sequences with different approaches, including analysis of peptide fragments by mass spectrometry [65,66,39], tagging the glutamine residues by TGase [68,69], or protein homology searching in edible grains [70]. Overall, a consistent number of peptides have been identified so far, derived from wheat (α-, γ-, ω-gliadins, glutenins) and, to a lesser extent, from barley and rye (respectively from the prolamins hordeins and secalins), that are able to activate intestinal CD4+ T cells from CD patients ( Table 1).…”
Section: In Vitro and In Vivo Tools For The Identification Of Prolamimentioning
confidence: 99%
“…These in vitro studies identified stimulatory gluten sequences with different approaches, including analysis of peptide fragments by mass spectrometry [65,66,39], tagging the glutamine residues by TGase [68,69], or protein homology searching in edible grains [70]. Overall, a consistent number of peptides have been identified so far, derived from wheat (α-, γ-, ω-gliadins, glutenins) and, to a lesser extent, from barley and rye (respectively from the prolamins hordeins and secalins), that are able to activate intestinal CD4+ T cells from CD patients ( Table 1).…”
Section: In Vitro and In Vivo Tools For The Identification Of Prolamimentioning
confidence: 99%
“…TG-catalyzed reaction was carried out at pH 6.8 and 8.0, according to Mamone et al [11], because of the influence of pH on the TG activity (lowering pH reactions are switched from transamidation to deamidation) [4]. Digested gliadins (0.5 mg/mL) was solved in 70 mM Tris-HCl buffer, containing 1 mM dithiothreitol and was incubated with TG (0.3 U/mg gliadin) for 2h at 43°C.…”
Section: Gliadinsmentioning
confidence: 99%
“…In order to detect gliadin peptides derived from gastric and pancreatic digestion possibly modified by tTG, a peptidomic analytical approach capable of selective probing of susceptible Q was developed. 77 The whole gliadin fraction, isolated from a winter wheat flour variety was hydrolysed using pepsin and trypsin (PT) to simulate in vivo digestion. Analysis by LC/MS of the PT digest showed the presence of a very large number of unresolved peaks (Fig.…”
Section: Characterisation Of Cross-linking and Deamidation Of Gliadinmentioning
confidence: 99%